Efektivitas Dana Desa Terhadap Pembangunan Desa Tunjungmuli Kecamatan Karangmoncol Kabupaten Purbalingga - Wardhana, Wisnu Eka; Firdausy, Adriana Grahani (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2022)
This study reviews how the Tunjungmuli Village government regulates and manages village funds obtained from the Central Government. In addition, this study identifies the level of effectiveness of Tunjungmuli Village Fund Management. This research is an empirical research. Has a descriptive analytical research nature with the aim of providing a detailed description or detail supported by a sociological juridical approach. Types and sources of research data used include primary and secondary. Data collection was done by interview and document study. The use of qualitative data analysis techniques produces data in descriptive form. The implementation of the management of Tunjungmuli Village village funds whose use priority is mandated in the Regulation of the Minister of Villages for Development of Disadvantaged Regions and Transmigration Number 13 of 2020 concerning Priority for the Use of Village Funds in 2021, unfortunately, not all indicators can be met by the Tunjungmuli Village Government. But in essence, most of the predetermined indicator points have been well fulfilled by the Tunjungmuli Village Government. In managing its village funds, the Tunjungmuli Village Government has been able to effectively realize the village funds that have been obtained. The realization of village funds in Tunjungmuli Village is divided into four (4) areas of implementation, namely the field of village administration, the field of implementation of village development, the field of community empowerment, and the field of disaster, emergency and urgent management.